The Scanian Economic-Demographic Database (SEDD) - Martin Dribe; Luciana Quaranta (Historical Life Course Studies)
The Scanian Economic-Demographic Database (SEDD) is a high-quality longitudinal data resource spanning the period 1646-1967. It covers all individuals born in or migrated to the city of Landskrona and five rural parishes in western Scania in southern Sweden. The entire population present in the area is fully covered after 1813. At the individual level, SEDD combines various demographic and socioeconomic records, including causes of death, place of birth and geographic data on the place of residence within a parish. At the family level, the data contain a combination of demographic records and information on occupation, landholding and income. The data for 1813-1967 was structured in the model of the Intermediate Data Structure (IDS). In addition to storing source data in the SEDD IDS tables, a wide range of individual- and context-level variables were constructed, which means that most types of analyses using SEDD can be conducted without the need of further elaboration of the data. This article discusses the source material, linkage methods, and structure of the database.